The clockmaker's wife - Wood, Daisy (Avon, 2021)
When she, while going through her grandmother's possessions, discovers a beautiful watch concealed in the back of a picture frame, Elizabeth is plunged into a World War II mystery involving a Jewish clockmaker and his young wife.